Features of the Political and Legal Justification of the Use of Force in Internal Armed Conflicts in Countering Terrorism and Other Violent Manifestations of Extremism - S. V. Korostelev (Управленческое консультирование)
In any specific case of the use of armed violence, the question of its legitimation arises, that is, the need to justify the validity of an act  of use of force in the language of the law. In general, the model of  the legal regime for the use of force to counter terrorism and other manifestations of violent extremism converges to a search for  a balance between norms applied, depending on the forces, means  and methods of warfare used: the norms of International  Humanitarian Law are to be applied to a greater extent when  antigovernment groups maintain control of a part of territory of a  state, International Human Rights Law — in the course of “law  enforcement” actions, when antigovernment forces do not exercise  such a control. The author describes the features of the political- legal rationale of the use of force in internal armed conflicts  interrelated with countering terrorism and other violent  manifestations of extremism:• there are important peculiarities that unify differing rules of law applicable to the international armed conflict, and applicable to  internal armed conflict and other situations of violence;• there are sovereign restrictions on the application of international law in internal armed conflicts and other situations of violence;• there are modern agreed restrictions on the use of means and methods of warfare in internal armed conflicts and other situations of violence;• as a result, joint regulations comprise a highly specific share of customary international law and a significant amount of «law enforcement» norms.